Perfil Fermentativo e Valor Nutritivo de Silagem de Capim-Elefante Inoculada com Streptococcus Bovis - Ferreira, D. J.; Zanine, A. M.; Santos, E. M.; Lana, R. P.; Silva, W. L. [UNESP]; Souza, A. L.; Pereira, O. G. (My University, 2011)
The experiment was developed to evaluate the effect of strains of Streptococcus bovis (HC5 and JB1) on pH, ammonia production and nutritional value in elephant-grass silages (Pennisetum purpureum Schum). The experimental design was entirely randomized, with three treatments: T1 - elephant- grass, T2 - grass-elephant inoculated with Streptococcus bovis HC5, T3 - elephant grass inoculated with Streptococcus bovis JB1, totaling five replicates per treatment. The smallest value of ammonia was observed in the silage treated with inoculante the base Streptococcus bovis JB1 (5.90% N-total). Inoculation increased the levels of lactic acid and decreased levels of acetic, propionic and butyric acids, and the silages inoculated with Streptococcus bovis JB1 and HC5 were those with the highest values of lactic acid. There were not statistical differences for the tenors of dry matter (MS) and crude protein (PB). For the values of the fibers, the grass-elephant silage inoculated with Streptococcus bovis JB1, it presented the smallest value of neutral detergent fiber (59.77 %) and Hemicellulose (26.71 %). The largest value of in vitro dry matter digestibility (DIVMS) was observed in the silage with Streptococcus bovis JB1, showing superiority of four percentile points (64.23 %) in relation to the treatment without bacterial inoculante (60.35 %). The use Streptococcus bovis JB1 was efficient in the process fermentativo besides promoting would get better in the quality of the fiber and DIVMS in the studied silage.
Fermentation and nutritive value of elephant grass silage inoculated with Streptococcus bovis
Keywords: Ammonia; Fiber; Forage; pH; Protein; Bacteria (microorganisms); Pennisetum; Pennisetum purpureum; Streptococcus bovis